2018
DOI: 10.7904/2068-4738-ix(17)-31
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the quality of the steamed yoghurts enriched by dates flesh and date powder variety H’loua

Abstract: Abstract. The purpose of the present work was to investigate the effect of including date flesh and date powder in the steamed yoghurt processing on some quality during four weeks of storage. In order to obtain the powders, date variety of H'loua was washed, cut into small particles, and then dried at 90 °C during 2 h. Seven steamed yoghurts were manufactured: control prepared by 80 g/L sucrose, yoghurts manufactured by replacement of some quantity of sucrose by 10, 20 and 25 g/L of the date powder and yoghurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…Lactose is the main sugar present in milk, a lactic acid fermentation substrate for lactic acid bacteria (Labioui et al, 2009). In addition, the consumption of fermented milk products has increased in recent years, mainly because of its excellent nutritional and therapeutic properties (Hariri et al, 2018). Our study showed that the average concentration of raw lactose bovine milk is 6.35 ± 0.89%.…”
Section: Storage Temperature Of Raw Milk In the Various Sales Outletsmentioning
confidence: 60%
“…Lactose is the main sugar present in milk, a lactic acid fermentation substrate for lactic acid bacteria (Labioui et al, 2009). In addition, the consumption of fermented milk products has increased in recent years, mainly because of its excellent nutritional and therapeutic properties (Hariri et al, 2018). Our study showed that the average concentration of raw lactose bovine milk is 6.35 ± 0.89%.…”
Section: Storage Temperature Of Raw Milk In the Various Sales Outletsmentioning
confidence: 60%
“…The foods in this way suffer different manipulations to meet the needs to offer immediately but also be merchant: the product has to last a long time in spite of transportation, refrigeration, it must remain on the store shelves and in the consumer's homes. 5 Unfortunately, in many cases, losing land is almost always the natural and fragile product. Similarly, a serial product, appropriate in shape and appearance to the sales requirements, will have more "value" than a non-homogeneous, non-standard product and more difficult to manage.…”
Section: Introductionmentioning
confidence: 99%
“…Dates have been used in several food preparations in order to replace added sugar. Date was used in the preparation of yoghurt in the form of syrup [GAD et al, 2010] , fiber [HASHIM et al, 2009] and powder [HARIRI et al, 2018] and for the preparation of soft drink in the form of powder [HARIRI et al, 2017] .…”
Section: Introductionmentioning
confidence: 99%